Inflammatory manifestations of Herpesviridae infection in the anterior segment of the eye - Radosavljevic, Aleksandra (Medical Research, 2024)
Introduction: Herpesviridae is a large family of double-stranded DNA viruses out of which eight types infect humans: Herpes simplex virus (HSV) type 1 and 2, Varicella zoster virus (VZV), Cytomegalovirus (CMV), Epstein Barr virus (EBV), Human herpesvirus (HHV) 6, 7 and 8. Herpetic eye disease can affect anterior and/or posterior segment of the eye. In this article we focused on the anterior segment manifestations.Methods: A review of research articles with key words scleritis, keratitis, anterior uveitis, herpetic, HSV, VZV, CMV, and EBV published in PubMed database until April 30th, 2024 was done.Results: HSV1, VZV, and CMV are well known to cause inflammation in the anterior segment of the eye, which includes episcleritis, scleritis, keratitis, and anterior uveitis or their combination. However, there are reports of anterior segment inflammation caused by EBV, HSV2, or HHV6. The disease usually has a recurrent or chronic course and persistent inflammation can cause severe damage to the ocular tissues, which can significantly impair vision. Although some types of ocular inflammation can be effectively treated with antiviral agents during active phase of the disease (HSV1, HSV2, VZV, CMV), so far there is no final treatment which would permanently prevent the recurrences. The main complications include corneal scarring, scleral thinning, glaucoma, synechiae, iris atrophy, and cataract.Conclusion: Due to its’ recurrent or chronic course, the herpetic inflammation of the anterior segment of the eye still remains a challenge for the clinician. Although in some cases there are typical clinical clues that lead an ophthalmologist to suspect the herpetic cause of the inflammation, the final diagnosis (especially in atypical cases) can be reached only by verification of viral genome from ocular tissues using PCR or in cases of uveitis the detection of local production of antiviral antibodies in the aqueous humor using Goldmann-Witmer coefficient.
Keywords: Herpetic eye disease; scleritis; keratitis; anterior uveitis; Herpesviridae; HSV; VZV; CMV